Byzantine plate and Frankish mines: the provenance of silver in north-west European coinage during the Long Eighth Century (c. 660–820) - Kershaw, JF; Merkel, S; Naismith, R; D'Imporzano, P (Cambridge University Press, 2024)
The late seventh century introduction of silver coinage marked a transformation in the economy of North-West Europe, yet the source(s) of silver bullion remains enigmatic. Here, we provide new insights into European silver sources through the ‘long eighth century’ (c. 660-820 AD) via the lead isotope and trace element analysis of 49 coins from England, Frisia and Francia. The results indicate an early reliance on Byzantine silver, followed from c. 750 by a shift to metal from Frankish mines. They generate new insights into the motives for minting, and reveal the strong role of the state in controlling metal resources.